Wisdom in Language and Quranic Context - Al-Jabouri , Muthana (Islamic Sciences Journal, 2023)
Wisdom is one of the Arabic words which is of one origin for it means bridling beasts and preventing impudence as well. This word has been reported in both poetry and prose. The word wisdom in holy Quran implies a lot of meanings. It is identified in the Quranic context as having the following meanings :( Quran, the prophetic Sunnah, prophecy, understanding, the Bible, credibility in talk and action, knowledge in religion, Quran sciences, preaching, mind, devoutness, and lest). All these words and the ones that are similar to them refer to wisdom because of Quranic context. It is to be mentioned that some interpreters disagree in interpreting the meaning of the word (wisdom) reported in one verse due to the overlapping and the credibility of them more than the others; however, we can conclude the appropriate meaning through reading it thoughtfully and understanding the whole context. In this study, I aimed at presenting all the meanings of the word (wisdom) that the interpreters have mentioned in the Quranic context. Some of them were compatible and close whilst others were so far in meaning.